Are we retaining our Maori talent? : representative youth netballers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - McCausland-Durie, Yvette (Massey University, 2007)
A case study research method was employed to address the question of retention for Māori youth netballers. Despite the fact that young Māori are well populated in the junior age groups of representative netball, a decline at the senior representative levels is apparent. This decline was particularly evident during the period of adolescence contributing to the research focus. Exploring the retention factors relative to this group required consideration of these three interrelated domains: education, gifted and talented education, and sport. Previous studies related to Māori Education, Māori in Sport, and Gifted Females led to this research. The findings highlighted three key themes: intrapersonal, interpersonal and structural factors. These factors are underpinned by cultural elements which when amalgamated become critical contributors to retention. As such, this research revealed that there is no single factor that will predictably lead to the fulfillment of retention issues for Māori female youth however several conclusions have been drawn. Firstly that the challenge of balancing multiple, and often, conflicting roles as students, athletes, females and Māori is reflective of racial and gender stereotypes in society. Secondly, that our policies in education and sport need to reflect that 'being Maori' is understood in a broader context encompassing both Māri and non-Māori. In practice, operations which reflect Kaupapa Māori principles will further enhance the participants self efficacy which will lead to improved experiences. Enhancing participants' quality of experiences in education and sport requires a recognition that access as a predecessor to retention greatly impacts on the institution or organizations ability to maintain Māori youth interest levels.
Keywords: Women netball players; New Zealand; Maori (New Zealand people) -- Sports; Women, Maori; Youth, Maori